2022
DOI: 10.3390/f13091401
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Bioinformatics and Expression Analysis of TCP Transcription Factors in Liriodendron chinense Reveals Putative Abiotic Stress Regulatory Roles

Abstract: As a magnoliid angiosperm, the Liriodendron chinense (Hamsl) Sarg in the Magnoliaceae family is susceptible to external environmental factors. The TEOSINTE BRANCHED 1/CYCLOIDEA/PROLIFERATING CELL FACTORS (TCP) proteins known for their growth and developmental biological roles have been identified in various plant species but not in the Liriodendron chinense. In this study, 15 TCP genes were identified in the L. chinense genome, and categorized into two classes, termed class I (PCF) and class II (CIN and CYC/TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Afterwards, total RNA was extracted from L. chinense seedlings treated at 0, 6, 24 h and 3d using a chloroform-free plant total RNA extraction kit from BioTeke Corporation and subjected to qRT-PCR analysis. Primer5.0 was used to create all of the primers for qRT-PCR ( Li et al., 2022a ; Hwarari et al., 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, total RNA was extracted from L. chinense seedlings treated at 0, 6, 24 h and 3d using a chloroform-free plant total RNA extraction kit from BioTeke Corporation and subjected to qRT-PCR analysis. Primer5.0 was used to create all of the primers for qRT-PCR ( Li et al., 2022a ; Hwarari et al., 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…The NCBI-CDD database ( , accessed on 15 September 2022) and SMART website ( , accessed on 15 September 2022) were used to predict the conserved domain of HSPs in L . chinense [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis concurred with previous TCP protein structure investigations (Pilar Cubas et al, 1999). Recently, we have also analysed the TCP protein structure of the L. chinense , and showed that most of the LcTCP proteins carry 2 to 3β-strands, and 2α-helices with alternating hydrophobic regions and are less mobile ( Hwarari et al, 2022 ). Other researches have also exhibited that the TCP protein contain potential sites of phosphorylation and regions linked by a conserved Glycine-Aspartate-Serine residues, highly frequent in loops and Proline ( Cubas et al, 1999 ; Tarczewska and Greb-Markiewicz, 2019 ; Edwards and Gorelick, 2022 ).This result generally confirms that the TCP bHLH domain is rather distinct from the bHLH domain.…”
Section: Tcp Conserved Domainsmentioning
confidence: 99%
“…Although their ancestry remains unknown ( Navaud et al, 2007 ), their biological roles and mode of action are conserved in plant species from the bryophytes to the angiosperms. Up to date, there have been several breakthroughs in the identification and computation of TCP TFs in numerous plant species including: A. thaliana ( Aggarwal et al, 2010 ), G. biloba ( Yu L. et al, 2022 ), P. edulis ( Liu et al, 2018 ), S. lycopersicum ( Parapunova et al, 2014 ), L. chinense ( Hwarari et al, 2022 ), etc. However, in some plant orders, the TCP TFs have not yet been identified ( Manassero et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation